PEMETAAN ASESMEN DIAGNOSTIK KOGNTIF PEMBELAJARAN DALAM MODEL SINTAKS GROUP INVESTIGATION - Sofiyan Baihaki; Saparudin; Abdul Fattah; Suhirman (STKIP Subang, 2026)
This research is motivated by learning practices at MA NW Selaparang Kediri, West Lombok, where the Group Investigation (GI) model is implemented informally while also being utilized as a diagnostic assessment tool. The objectives of this study are to describe the diagnostic assessment model, analyze the syntax of the GI model, and explain the form of integration of diagnostic assessment into the GI model in the Qur'an and Hadith subject for eleventh grade. The research employs a qualitative approach with a case study design. Data collection techniques include participatory observation, in-depth interviews, and documentation. Data analysis consists of data condensation, data presentation, and conclusion drawing with verification. The results show that: (1) the diagnostic assessment model applied is a simple oral assessment at the beginning of the semester to identify students’ learning readiness and group preferences, (2) the syntax of the GI model comprises five stages: group formation based on oral assessment, topic identification and task planning, collaborative paper writing, presentation, and structured question-and-answer sessions with teacher evaluation, (3) the integration of diagnostic assessment into the GI model occurs at two points: as the basis for group formation and through the question-and-answer session used by the teacher to map students’ learning difficulties.